2008
DOI: 10.1161/strokeaha.107.501643
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Rural Areas and Small Communities

Abstract: Abstract-The management of stroke in rural and regional areas is variable in both the developed and developing world.Informed by best-practice guidelines and recommendations for systems of stroke care, adaptable models of care that are appropriate for local needs should be devised for rural and regional settings. This review addresses the issue of the provision of appropriate services in rural and regional settings, with particular attention to the barriers involved, according to the classification of Low Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 57 publications
2
84
2
5
Order By: Relevance
“…Most of the studies have described the use of technology solutions, principally to support rehabilitation activities (Hersh et al 2006). Joubert et al (2006;2008a;2008b) examined the effect of a telemedicine intervention on risk factor management and depressive symptoms in the ICARUSS study. Despite the published importance of implementation of best-practice management principles, this is the only telestroke study that has addressed risk factor management directly and shown results in an RCT.…”
Section: Importance Of Preventive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies have described the use of technology solutions, principally to support rehabilitation activities (Hersh et al 2006). Joubert et al (2006;2008a;2008b) examined the effect of a telemedicine intervention on risk factor management and depressive symptoms in the ICARUSS study. Despite the published importance of implementation of best-practice management principles, this is the only telestroke study that has addressed risk factor management directly and shown results in an RCT.…”
Section: Importance Of Preventive Strategiesmentioning
confidence: 99%
“…Therapeutic inertia associated with the long-term management of these risk factors remains common at primary care level and in order to address this, a combination of a 'hub-and-spoke' case management model (care coordinator, with multiple stroke survivors) with a linear 'top-down' model (specialist, coordinator, carer, patient and primary care physician) could be advantageous. The ICARUSS model by Joubert et al (2006;2008a;2008b) provides an example of a telestroke model which specifically supports the implementation of secondary stroke prevention strategies and the detection of post stroke depression. Hersh et al (2006) found that there were only a small number of well-designed telestroke studies, particularly in rural settings.…”
Section: Future Trends and Recommendationsmentioning
confidence: 99%
“…Ancak gerek dünyada gerekse ülkemizde inme hastalarına uygun tedavi verilmesi oranları istenilen seviyenin altındadır. İnme hastalarıyla ilgili bu sorunu gidermek için özellikle gelişmiş ülkelerde durum tespitine yönelik ulusal çapta çalışmalar yapılmakta, çözüm önerileri sunulmakta ve bu önerilerin uygulanmasını takiben elde edilen başarı oranları incelenmektedir (6,7,8). Ülkemizde de konuyla ilgili bazı üniversite inme merkezlerinin bildirmiş olduğu veriler yayınlanmıştır.…”
Section: Introductionunclassified
“…Globally, the majority of strokes occur in rural areas which are often underserviced [9]. In rural areas, stroke care is often fragmented and does not adhere to recommended guidelines [9, 10].…”
Section: Introductionmentioning
confidence: 99%